CB‐TE2A+·Cl−·3H2O: a short intermolecular hydrogen bond between zwitterionic bicyclo[6.6.2]tetraamine macrocycles. Issue 2 (19th January 2016) - Jurek, Paul; Reibenspies, Joseph H.; Kiefer, Garry E.
Abstract : The crystal structure of CB‐TE2A + ·Cl − ·3H2 O is reported together with its comparison to closely related structures. The reason the macrocycle forms complexes with copper ions slowly is discussed. Abstract : 1, 4, 8, 11‐Tetraazabicyclo[6.6.2]hexadecane‐4, 11‐diacetic acid (CB‐TE2A) is of much interest in nuclear medicine for its ability to form copper complexes that are kinetically inert, which is beneficial in vivo to minimize the loss of radioactive copper. The structural chemistry of the hydrated HCl salt of CB‐TE2A, namely 11‐carboxymethyl‐1, 8‐tetraaza‐4, 11‐diazoniabicyclo[6.6.2]hexadecane‐4‐acetate chloride trihydrate, C16 H31 N4 O4 + ·Cl − ·3H2 O, is described. The compound crystallized as a positively charged zwitterion with a chloride counter‐ion. Two of the amine groups in the macrocyclic ring are protonated. Formally, a single negative charge is shared between two of the carboxylic acid groups, while one chloride ion balances the charge. Two intramolecular hydrogen bonds are observed between adjacent pairs of N atoms of the macrocycle. Two intramolecular hydrogen bonds are also observed between the protonated amine groups and the pendant carboxylate groups. A short intermolecular hydrogen bond is observed between two partially negatively charged O atoms on adjacent macrocycles. The result is a one‐dimensional polymeric zigzag chain that propagates parallel to the crystallographic a direction. A second intermolecular interaction is a hydrogen‐bonding network in the crystallographic b direction. The carbonyl group of one macrocycle is connected through the three water molecules of hydration to the carbonyl group of another macrocycle.